Burnout Integrative Measure: A preliminary validation among French college students - Berjot, Sophie; Weber, Tiphanie; Huyghebaert-Zouaghi, Tiphaine (Frontiers in Psychology, 2022)
The aim of this research was to create and validate an integrative measure of college students’ burnout. A burnout measure was proposed and extended the three-dimensional conceptualization of burnout (weariness, detachment toward social objects, inadequacy). Based on prior research, our conceptualization and measure distinguished between types of weariness (cognitive, physical, and emotional weariness) and between different targets of detachment toward social objects (studies, other students, teachers). We also relied on negatively worded items to assess inadequacy, as suggested in the literature. The criterion-related validity of our Burnout Integrative Measure (BIM) was examined by exploring associations with two closely related constructs, namely stress and depression. Results from structural equation modelling provided support for a second-order model encompassing the different targets of detachment, the distinct types of weariness, and inadequacy. Correlations with related constructs (depression and stress) mostly confirmed our hypotheses. Results and practical implications are discussed.